Structural and functional alterations of intestinal flora in mice induced by halonitromethanes exposure - Yin, Jinbao; Li, Dingxin; Zheng, Tianming; Wang, Xun; Hu, Bin; Wang, Peifang (Frontiers in Microbiology, 2022)
Halonitromethanes (HNMs) as one typical class of nitrogenous disinfection byproducts (DBPs) have been widely found in drinking water and are receiving more and more attentions because of their high cytotoxicity, genotoxicity, and developmental toxicity. However, the effects of HNMs exposure on the intestinal tract and intestinal flora remain unknown. This study comprehensively determined the effects of trichloronitromethane, bromonitromethane, and bromochloronitromethane exposure on the intestinal tract and intestinal flora. Results showed that the three HNMs induced intestinal oxidative stress and inflammatory response. Further, HNMs exposure could change the diversities and community structure of intestinal flora, thereby triggering intestinal flora dysbiosis, which might be associated with the intestinal damage such as oxidative stress and inflammation. The intestinal flora dysbiosis was accompanied with mark alterations in function of intestinal flora, such as carbohydrate, lipid, and amino acid metabolisms. This research provides a new insight into studying the toxicity of HNMs exposure based on intestinal flora, which will further improve the health risk assessment of DBPs in drinking water.